Kinesiology Students' Perceptions of Ambivalent Sexism. Issue 3 (2nd September 2018) - Taylor, Elizabeth A.; Johnson, Alicia; Hardin, Robin; Dzikus, Lars
Abstract : The culture of sport has historically reinforced hegemonic notions of gender. Both intercollegiate and professional sports in the United States are male-dominated in employment numbers and leadership positions. This raises concerns about the professional work environment women will encounter in their careers. Thus, the purpose of this study was to examine perceptions of sexism among kinesiology students who will be entering the male-dominated sports workplace. The Ambivalent Sexism Inventory (ASI) was used to measure sexism (hostile and benevolent) among students enrolled in kinesiology-related majors at a large public university in the southeastern United States. Men scored significantly higher than women on both subscales. Undergraduate students also scored significantly higher than graduate students. Overall, the mean scores in this study were higher than those reported previously for other college student populations. The findings suggest considerable hostile and benevolent sexism among these students.